2022
DOI: 10.1037/emo0000940
|View full text |Cite
|
Sign up to set email alerts
|

Recalling fearful memories modifies approach and avoidance behavior based on spatial context.

Abstract: Motor responses are more efficient when there is a match (or congruency) between the motivational properties of an emotional state and the distance altering characteristics of the movement being executed to the emotion-eliciting stimulus. However, the role of spatial context in shaping motivational orientations to approach and avoid, particularly during whole-body movement tasks, remains less understood. We sought to narrow this knowledge gap by investigating whether an emotion (fear) relived from a previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Extemporaneous speech topics, while familiar and accessible to participants, may possess some inherent affective content (e.g., a pleasant memory of time spent with a friend, vividness of the imagery elicited by the memory, etc.). Researchers should therefore aim to explore the affective context of the speech monologue to potentially control for confounds from affect-induced changes in gait behavior (Fawver et al 2014 , 2022 ). Additionally, measuring lexical complexity and lexical ‘stageholders’ like filled pauses in extemporaneous speech should increase measurement sensitivity (Davie et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extemporaneous speech topics, while familiar and accessible to participants, may possess some inherent affective content (e.g., a pleasant memory of time spent with a friend, vividness of the imagery elicited by the memory, etc.). Researchers should therefore aim to explore the affective context of the speech monologue to potentially control for confounds from affect-induced changes in gait behavior (Fawver et al 2014 , 2022 ). Additionally, measuring lexical complexity and lexical ‘stageholders’ like filled pauses in extemporaneous speech should increase measurement sensitivity (Davie et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies wherein facial expression recognition affected approach–avoidance behavior demonstrated that compared to seeing a happy facial expression, seeing an angry expression results in the individual maintaining a larger interpersonal distance from another [2,3] and a slower approach [1]. Further, other studies have suggested a fast avoidance response to threats [1214,16,28]. These studies support the association between anger and avoidance, indicating that the purpose is maintaining distance from the threatening other.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, researchers should explore the affective context of the speech monologue to potentially control for confounds from affect-induced changes in gait behavior. 67,68 Finally, measuring lexical complexity and lexical 'stageholders' like filled pauses in extemporaneous speech should be included in future studies. 69…”
Section: Limitations and Future Directionsmentioning
confidence: 99%